Characterisation of glass based on physical properties and scanning electron microscope coupled with energy dispersive x-ray spectroscopy - Nordin, Radziah (Universiti Sains Malaysia, 2016)
Glass is one of the important physical evidence in forensic science as it can link the suspect or assailant with the victims and crime science. It is frequently encountered at crime scenes, particularly those involving motor vehicle accidents or burglaries. This study emphasized on the characterization of two difference types of glass, laboratory and household glassware based on physical properties (thickness, density and refractive index) and elemental composition by SEM-EDX. Thickness analysis was divided into three parts, upper, middle and base. The thickness of upper part for laboratory glassware was found in the range of 1.41 mm - 2.02 mm while for household glassware was in the range from 3.06 mm - 4.09 mm. Next, the range for middle part of laboratory glassware was 2.88 mm - 3.48 mm while household between 1.41 mm - 2.02 mm. Then, the thickness for base part of laboratory glassware was in the range between 0.9 mm - 4.16 mm while for household glassware in the range 4.22 mm - 5.06 mm. The density of laboratory glassware also different with the household glassware as lab glass has density 2.2 gem 3 while household was 2.4 gem 3 Other than that, the refractive index for the laboratory glassware showed the range between 1.472 - 1.506 while for the household glassware gave the refractive index from 1.515 - 1.522. Next, for the elemental composition detection by using SEM-EDX has identified all expected elements (Si, Ca, Mg, Na, C, O, Al, K.) except for boron (B).